EFEKTIFITAS MASSAGE COUNTER PRESSURE PADA INTRANATAL KALA I FASE AKTIF DI RSUD DR. SOEDIRMAN KEBUMEN - Eko Riyanti; Nova Ari Pangesti; Dwi Rizki Arianti (AKPER Pemkab Purworejo, 2022)
Background: Asthma is the tenth leading cause of morbidity and mortality in Indonesia with a prevalence of 2.4%. Asthma causes respiratory problems in the form of wheezing, shortness of breath, coughing and difficulty breathing, especially at night. Many children receive irrational treatment, do not receive proper prevention so that the disease can progress to a more serious condition. One of the appropriate therapy in this case is blowing balloon therapy. The purpose of this study was to determine the effect of balloon blowing on oxygenation status in children with bronchial asthma. The research method used was a case study with a sample of 2 participants aged 9 and 5 years. Collection techniques using interviews, observation and documentation studies. Results: Based on the case study, it was shown that after balloon blowing therapy was carried out in children with bronchial asthma it was effective in reducing shortness of breath, reducing respiratory frequency to normal, overcoming wheezing and increasing oxygen saturation. Conclusion: There is an effect of balloon blowing technique therapy in pediatric patients with bronchial asthma on oxygenation status. Suggestion: Balloon Blowing Therapy (blowing balloons) can be used as a non-pharmacological therapy for children with bronchial asthma which is carried out 3 days every morning with a duration of 20 minutes.